Efficacy of Mindfulness on Perceived Stress and Blood Pressure Control in Patients with Type 2 Diabetes - Mohammad Kazem Fakhri; Adele Bahar; Fatemeh Amini (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Mindfulness reduces stress and blood pressure in patients with chronic diseases. The aim of this research was to study the effectiveness of mindfulness on perceived stress and blood pressure control in diabetic patients. Materials and methods: This clinical trial was performed in 50 patients with type-2 diabetes attending Touba Endocrine Clinic, Sari, Iran. They were divided into control (n=25) and intervention (n=25) groups. The training program consisted of 10 weekly sessions. Perceived stress was investigated in participants using Cohen's Perceived Stress Scale before and after the intervention. The levels of blood pressure were recorded before and after the intervention. Results: In experimental group, there was a significant decrease in perceived stress in posttest (11.60 ± 1.55) compared with that in pretest (13.96 ± 1.84) (r=0.293, P= 0.001). But no significant difference was found in the scores of the control group (P= 0.619). The mean blood pressure level showed a significant reduction in case group (r= 0.183, P= 0.001) but it was not significantly different in control group (P=0.409). The mean blood pressure level in experimental group was significantly lower after the intervention (10.72±0.89) compared with that before the intervention (13.08±2.04) (r=0.293, P=0.001). Conclusion: In current study, mindfulness training reduced the perceived stress and levels of blood pressure.